REVITALISASI TEMBANG TEKS SASTRA BALI TRADISIONAL DALAM RANAH RITUAL DAN DIGITAL - Putra, I Nyoman Darma; Sari, Ida Ayu Laksmita (ATAVISME, 2019)
There has been a concern that textual singing tradition (kidung) may disappear along with the advancement of information and communication technology. This paper aims to examine the metamorphosis of kidung from the ritual realm to the digital domain which is the basis of today's electronic mass media. Data were collected with ethnographic method and interviews with enthusiasts and audiences of kidung as well as with managing of electronic mass media. Recording method was used to record the interactive kidung programme in Radio and TV. The data were examined by transformation media and globalization theory. The study began with a description of the metamorphosis of kidung from the ritual realm to digital, enthusiasts and audiences, as well as the future of the kidung cultural heritage in the digital era. The result shows that the transformation of kidung from the ritual to the digital domain is a revitalization process that makes this tradition increasingly lively, not vanishing as it has been feared. In addition, the tradition of the kidung which was originally dominated by the older generation, has also been able to attract younger generation who present it through digital-based social media such as Facebook and YouTube so that it can be enjoyed by Balinese diaspora.